IOT BASED SMART HOME SIMULATION (INTERNET OF THINGS) - Ardianto, Yeheskiel Hency; Widiasari, Indrastanti Ratna (STMIK Royal, 2024)
Abstract: The development of Internet of Things (IoT) technology has significantly impacted life, particularly in creating more efficient and secure smart homes. Smart homes integrate various electronic devices to enhance comfort and energy efficiency. However, cost, integration complexity, and security issues remain. This study will simulate an IoT-based smart home system to analyse and evaluate device performance before real-world implementation. The simulation method involves testing connectivity and evaluating delay and packet loss using the ping method on each device. Results show the highest delay on CCTV devices at 41.8 ms and the lowest on motion detector 2 at 32.8 ms, with 0% packet loss. According to TIPHON standards, the network is rated excellent with an index of 4. The designed smart home system demonstrates optimal performance and is feasible for implementation but requires further development in configuration using AI and machine learning technologies. Keywords: internet of things; simulation; smart home; testing Abstrak: Perkembangan teknologi Internet of Things (IoT) telah membawa perubahan signifikan dalam kehidupan, terutama dalam pengembangan rumah pintar (smart home) yang lebih efisien dan aman. Smart home mengintegrasikan berbagai perangkat elektronik untuk meningkatkan kenyamanan dan efisiensi energi. Meskipun demikian, tantangan seperti biaya, kompleksitas integrasi, dan isu keamanan masih ada. Penelitian ini bertujuan untuk mensimulasikan sistem smart home berbasis IoT guna menganalisis dan mengevaluasi kinerja perangkat sebelum implementasi nyata. Metode simulasi yang digunakan melibatkan pengujian konektivitas dan evaluasi delay serta packet loss dengan metode ping pada setiap perangkat. Hasil menunjukkan delay tertinggi pada perangkat CCTV sebesar 41.8 ms dan terendah pada motion detector 2 sebesar 32.8 ms, dengan packet loss 0%. Berdasarkan standar TIPHON, jaringan dinilai sangat baik dengan indeks 4. Sistem smart home yang dirancang menunjukkan kinerja optimal dan layak diimplementasikan, namun masih memerlukan pengembangan lebih lanjut dalam konfigurasi menggunakan teknologi AI dan machine learning. Keywords: internet of things; pengujian; simulasi; smart home